Peran Kesehatan dan Keselamatan Kerja (K3) serta Motivasi terhadap Produktivitas melalui Kepuasan Kerja - Nur Shafira Putri; Muhammad Idris; Diah Isnaini Asiati (Universitas Muhammadiyah Palembang, 2025)
Purpose – This study aims to determine the influence of Occupational Health and Safety (OHS) and motivation on employee productivity at PT. Pupuk Sriwijaya Palembang. This research is associative in nature. The variables used in this study are Occupational Health and Safety (OHS), motivation, job satisfaction, and employee productivity. Design/methodology – The sample consists of 120 employees of PT. Pupuk Sriwidjaja Palembang, selected using Cluster Random Sampling. The data used in this study is primary data collected through questionnaires. The data analysis technique employed is Structural Equation Modeling (SEM) using the Lisrel software. Findings - The results of this study show that: Occupational Health and Safety (OHS) has a positive and significant effect on Job Satisfaction, Motivation has a positive and significant effect on Job Satisfaction, Occupational Health and Safety (OHS) has a positive and significant effect on Employee Productivity, Motivation has a positive and significant effect on Employee Productivity,) Job Satisfaction has a positive and significant effect on Employee Productivity, Occupational Health and Safety has a positive and significant effect on Employee Productivity through Job Satisfaction, Motivation has a positive and significant effect on Employee Productivity through Job Satisfaction at PT. Pupuk Sriwijaya